Teacher Professional Development in Finland: Towards a More Holistic Approach - Hannele Niemi (Psychology, Society & Education, 2015)
The article reflects on teacher professional development as a continuum that starts during pre-service time, continues into the first years of newly qualified teachers’ induction phase, and spans a career-long development throughout their teaching careers. Finnish teachers work in contexts that provide high professional autonomy and agency in their work. Pre-service teacher education prepares them for this responsible role. In earlier years, in-service training occurred on training days and through short courses. The new trend sees teachers as developers in the whole school community. Teachers have research-based orientation in pre-service teacher education, which makes them capable to design school-based projects and their own development as it relates to school development. The article introduces four cases in which new trends have already been implemented. These best practices are examples how to (1) support the school community to cross boundaries towards multi-professional cooperation, (2) design an innovative school community using a design-based approach together with many partners, (3) connect pre-service and in-service research-based teacher education in science, technology and math (STEM) teaching, and (4) promote induction for new teachers.